Suppression of STAT5 Functions in Liver, Mammary Glands, and T Cells in Cytokine-Inducible SH2-Containing Protein 1 Transgenic Mice - Matsumoto, Akira (American Society for Microbiology, 1999)
Various cytokines utilize Janus kinase (JAK) and the STAT (signal transducers and activators of transcription) family of transcription factors to carry out their biological functions. Among STATs, two highly related proteins, STAT5a and STAT5b, are activated by various cytokines, including prolactin, growth hormone, erythropoietin, interleukin 2 (IL-2), and IL-3. We have cloned a STAT5-dependent immediate-early cytokine-responsive gene, CIS1 (encoding cytokine-inducible SH2-containing protein 1). In this study, we created CIS1 transgenic mice under the control of a β-actin promoter. The transgenic mice developed normally; however, their body weight was lower than that of the wild-type mice, suggesting a defect in growth hormone signaling. Female transgenic mice failed to lactate after parturition because of a failure in terminal differentiation of the mammary glands, suggesting a defect in prolactin signaling. The IL-2-dependent upregulation of the IL-2 receptor α chain and proliferation were partially suppressed in the T cells of transgenic mice. These phenotypes remarkably resembled those found in STAT5a and/or STAT5b knockout mice. Indeed, STAT5 tyrosine phosphorylation was suppressed in mammary glands and the liver. Furthermore, the IL-2-induced activation of STAT5 was markedly inhibited in T cells in transgenic mice, while leukemia inhibitory factor-induced STAT3 phosphorylation was not affected. We also found that the numbers of γδ T cells, as well as those of natural killer (NK) cells and NKT cells, were dramatically decreased and that Th1/Th2 differentiation was altered in transgenic mice. These data suggest that CIS1 functions as a specific negative regulator of STAT5 in vivo and plays an important regulatory role in the liver, mammary glands, and T cells.